Pengaruh kompetensi sumber daya manusia dan penerapan sistem akuntansi keuangan daerah terhadap kualitas laporan keuangan pemerintah daerah pada Badan Pengelolaan Keuangan dan Aset Daerah Kota Jambi - Cinta Bella Kristina Purba, Theresia; Zamzami, Zamzami; Hardiani, Hardiani (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to determine and analyze the influence of Human Resource Competency and the Implementation of Regional Financial Accounting Systems together (simultaneously) on the Quality of Regional Government Financial Reports. The data collection technique in this research was distributing questionnaires to 17 respondents of financial accounting and reporting employees using a descriptive quantitative approach method. Research data is primary data obtained directly through questionnaires distributed to research respondents. The analytical tool used is multiple linear regression with the help of SPSS 26 software. The results show that Human Resource Competency has a positive and significant effect on the Quality of Regional Government Financial Reports. The implementation of the Regional Financial Accounting System has no and no significant effect on the Quality of Regional Government Financial Reports. Human Resource Competency and Implementation of the Jambi City Regional Government Financial Accounting System together (simultaneously) have a positive and significant effect on the quality of Regional Government Financial Reports.